Usability Evaluation of the Indodax Website User Interface using Heuristic Evaluation and Severity Rating Methods - Imanuel Guardion Angel (SISTEMASI, 2026)
The growth of crypto-asset investment in Indonesia has increased the demand for trading platforms with good usability. This study aims to evaluate the usability of the Indodax website using Heuristic Evaluation based on Nielsen's ten usability heuristics and to determine improvement priorities using Severity Rating. A descriptive quantitative approach was employed, involving 13 active Indodax users as respondents. Data were collected through a Likert-scale questionnaire that was tested for validity, reliability, and normality. The results showed that all questionnaire items were valid, with the calculated r-values exceeding the critical r-value of 0.553. The instrument achieved a Cronbach's Alpha of 0.985, indicating very high reliability, while the Shapiro–Wilk normality test yielded a significance value of 0.377 (>0.05). The evaluation identified ten usability problems, consisting of two critical, six major, and two minor issues. Improvement priorities were focused on Error Prevention, User Control and Freedom, and Consistency and Standards to enhance the quality of the user interface, user experience, and transaction security of the Indodax website. The findings provide practical insights for prioritizing interface improvements and enhancing the overall usability and reliability of crypto-asset trading platforms.